2020
DOI: 10.1097/jcn.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mobile Health for Self-management of Cardiometabolic Risk Factors

Abstract: Background Although mobile health (mHealth) technologies are burgeoning in the research arena, there is a lack of mHealth interventions focused on improving self-management of individuals with cardiometabolic risk factors (CMRFs). Objective The purpose of this article was to critically and systematically review the efficacy of mHealth interventions for self-management of CMRF while evaluating quality, limitations, and issues with disparities using the technology accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…In another review, one article reported affordability problems related to the devices needed for the digital health solution, whereas other included studies found lower income to be a facilitator for engagement in digital solutions (47). Low socioeconomic status was found to be attributed to less utilization of digital health solutions in one review (40), whereas age appeared as a moderator for this association in another analysis (47). Within the layer of "living and working conditions, " education emerged as the most important determinant.…”
Section: Innovation Competitiveness Economic Growth and Digital Inmentioning
confidence: 99%
See 3 more Smart Citations
“…In another review, one article reported affordability problems related to the devices needed for the digital health solution, whereas other included studies found lower income to be a facilitator for engagement in digital solutions (47). Low socioeconomic status was found to be attributed to less utilization of digital health solutions in one review (40), whereas age appeared as a moderator for this association in another analysis (47). Within the layer of "living and working conditions, " education emerged as the most important determinant.…”
Section: Innovation Competitiveness Economic Growth and Digital Inmentioning
confidence: 99%
“…The PubMed search led to 35 results, of which 16 articles were included for analysis after the title and abstract assessment (Supplementary Material A). Nine of the identified studies focused on self-management support (40)(41)(42)(43)(44)(45)(46)(47)(48), two were related to health education and information (49,50), and five studies investigated digital health services (51,52) or health promotion and disease prevention interventions (53-55).…”
Section: Innovation Competitiveness Economic Growth and Digital Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially during the COVID-19 pandemic, with the suspension of many face-to-face medical and health care services, telehealth and telecommunication have been widely used to offset the loss of manpower within face-to-face medical services [ 2 ]. Furthermore, many forms of internet-based health technologies ease the daily lives of Americans by providing ways to self-manage their illnesses and conditions such as diabetes, physical activity, diet, weight loss, heart failure, and more [ 3 ]. These daily health technologies use combinations of already existing technologies that are updated with the current technology.…”
Section: Introductionmentioning
confidence: 99%